General solution:
DSolve[{x1'[t] == -x1[t] + x2[t], x2'[t] == x1[t] - x2[t]}, {x1[t], x2[t]}, t]
(*{{x1[t] ->
1/2 E^(-2 t) (1 + E^(2 t)) C[1] + 1/2 E^(-2 t) (-1 + E^(2 t)) C[2],
x2[t] ->
1/2 E^(-2 t) (-1 + E^(2 t)) C[1] +
1/2 E^(-2 t) (1 + E^(2 t)) C[2]}}*)
Or:
A = {{-1, 1}, {1, -1}};
DSolve[x'[t] == A . x[t], x[t] \[Element] Vectors[2], t]
(*{{x[t] -> {1/2 E^(-2 t) (1 + E^(2 t)) C[1] +
1/2 E^(-2 t) (-1 + E^(2 t)) C[2],
1/2 E^(-2 t) (-1 + E^(2 t)) C[1] +
1/2 E^(-2 t) (1 + E^(2 t)) C[2]}}}*)
Solution by series:
AsymptoticDSolveValue[{x1'[t] == -x1[t] + x2[t],
x2'[t] == x1[t] - x2[t]}, {x1[t], x2[t]}, {t, 0, 5}]
(*{(1 - t + t^2 - (2 t^3)/3 + t^4/3 - (2 t^5)/15) C[
1] + (t - t^2 + (2 t^3)/3 - t^4/3 + (2 t^5)/15) C[
2], (t - t^2 + (2 t^3)/3 - t^4/3 + (2 t^5)/15) C[
1] + (1 - t + t^2 - (2 t^3)/3 + t^4/3 - (2 t^5)/15) C[2]}*)